Interactive Media of Additives and Addictive Substances Based on Android as an Effort to Increase Learning Motivation of SMP / MTs Students - Eni, Nur; Nurmayanti, Nurmayanti; Madaling, Madaling (UNDIKMA, 2024)
The aims of this study were to: (1) create interactive learning materials based on Android; and (2) characterize the validity, practicality, and effectiveness of such materials in order to pique students' interest and boost their involvement in the material through engaging and interactive features. The five steps of the ADDIE model, which comprise research and development designs, are analysis, design, development, implementation, and evaluation. Both qualitative and quantitative descriptive data analysis was used in this study. With a percentage value of 92% (very valid), the results showed that the interactive learning media produced met the validity criteria. With a percentage value of 95.36% (very practical), the results of the field trial show that the interactive learning materials produced also meet the criteria of practicality. The trial findings show that interactive learning media increases students' learning motivation by fostering the drive and desire for achievement, supporting learning needs, creating a supportive learning environment, and fostering learning independence in the classroom. Based in these data, the conclusion that the outcomes of the interactive learning materials may be deemed valid, practical, and effective for use in the scientific teaching and learning process for class VIII SMP/MTs.